Quo Vadis Regulation on Underwater Cultural Heritage in Indonesia: Balancing Conservation and Economic Interest - Yuniza, Mailinda Eka; Merdekawati, Agustina; Talitha Putri, Gilda; Abraham Guntur, Jeremy (Udayana Journal of Law and Culture, 2022)
The management of underwater cultural heritage in Indonesia is still experiencing many obstacles, one of which is the imbalance between conservation and economic interest in managing underwater cultural heritage. The results indicate that these problems stem from the legal gap that exists in the Indonesian legal system. Existing Laws and Regulations have not been adequate to respond to the needs for conservation and proper economic utilization of underwater cultural heritage. The non-existent provision in regards to in situ and ex situ conservation, as well as the appraisal and selling methods, has led to further legal uncertainty. By using normative legal research methods, this research paper aims to analyze the urgency of managing valuable cargo objects from sunken ships classified as underwater cultural heritage objects and formulate a new concept of underwater cultural heritage management which contain seven steps that will balance both conservation and economic.